Adipogenic differentiation of culture-expanded bone marrow derived porcine mesenchymal stem cells - DHARA, SUJOY K; SANTRA, LAKSHMAN; GUPTA, SAURABH (The Indian Journal of Animal Sciences, 2017)
In order to use Mesenchymal stem cell populations for obesity and related metabolic syndrome studies in cell culture system, as a prerequisite, we evaluated the potency of these stem cells to undergo adipogenic differentiation. Porcine stem cells were chosen to study adipogenesis in due to the fact that pig has a natural tendency to get obese and the species is considered to be the most desired biomedical model for human applications. Porcine MSCs have been exposed to adipogenic induction media following a 21day protocol and observed under microscope for detecting stages of differentiation. At the terminal differentiation stage; morphologically, the cells appeared rounded with numerous large cytosolic lipid spheres. Upon staining with Oil Red O, the lipid spheres stained bright red. Based on this, proprietary medium was found to differentiate MSCs more efficiently than medium formulated on previous reports. Both, the differential morphologic feature corresponding to the adipocyte and positive Oil Red O staining confirmed about successful adipogenic differentiation. We envision that stem cell based culture system from porcine species would aid for studying molecular adipogenesis and subsequent identification of therapeutic targets for obesity and other metabolic diseases.